Why does a leader’s other-oriented perfectionism lead employees to do bad things? Examining the role of moral disengagement and moral identity - Jiang, Feng; Zhang, Weipeng; Zhang, Hongyan; Zhang, Zhe (Frontiers in Psychology, 2024)
Moral disengagement is an essential concept in organizational behavioral ethics, as it is strongly related to employee behaviors and attitudes. What is not clear, however, is which leader traits are directly associated with employees' moral disengagement and which are indirectly associated with unethical behavior. This study draws on a social cognitive perspective that links leaders' otheroriented perfectionism (LOOP) with unethical employee behavior. Specifically, we propose that LOOP provides employees with excuses and encouragement to engage in unethical proorganizational behavior (UPB). We analyzed data collected from 266 full-time employees at twotime points, and used mediated and moderated structural equation models to test the hypotheses, and the findings largely support our claims. The results suggest that LOOP effectively promotes employees' involvement in UPB. Moderated mediation tests suggest that the positive indirect impact of LOOP on employees' unethical behavior via moral disengagement was attenuated by higher employees' moral identity. In summary, the results indicate that when leaders emphasize only perfection and make unrealistic demands on their employees, the latter perceive that engaging in unethical behavior is demanded by the leader, that the responsibility is not theirs, and thus they are more willing to engage in unethical behavior. This study discusses the implications of these findings from both practical and theoretical perspectives.